Soil erosion and sediment flux in Northern Jordan : analysis, quantification and the respective qualitative impacts on a reservoir using a multiple response approach /: analysis, quantification and the respective qualitative impacts on a reservoir using a multiple response approach. (2016) - Kraushaar, Sabine
No abstract available